Transient glyphosate encephalopathy due to a suicide attempt - Saaya Yokoyama; Tomomi Sugisaki; Yoshida Ryota; Sato Yoshiteru; Hiroaki Okayasu; Mukuto Shioda; Keisuke Suzuki; Norio Yasui‐Furukori; Kazutaka Shimoda (Wiley, 2021)
Abstract Aim Glyphosate‐containing herbicides are less toxic than paraquat and are one of the most widely used herbicides today. Case presentation We report a case of ingestion of a pesticide containing glyphosate in a suicide attempt. The patient was admitted to the psychiatric department because of persistent suicidal thoughts. He suffered from short‐term memory impairment on day 3. Magnetic resonance imaging (MRI) showed swelling in the bilateral medial temporal lobes and hippocampi and high signal on T2‐weighted images. Gradually, the patient's cognitive impairments improved, and he was discharged on day 33. Conclusion A physician should examine the patient with the possibility of glyphosate encephalopathy in mind.